ANALISIS PELAYANAN DAN PERTUMBUHAN PAJAK HOTEL PASCA OPERASIONAL JALAN TOL PEKANBARU DUMAI DI KOTA DURI - Muslim Rahman; Nurul Fadhilah (Jurnal PubBis, 2024)
The areas traversed by the Pekanbaru-Dumai Toll Road, including Duri City, have experienced various dynamics. Duri, once known as a transit and rest city for drivers from different regions, has seen a decline in its role since the toll road became operational. Drivers now bypass Duri, heading directly to their destinations. This study aims to evaluate hotel service and tax growth in Duri City following the operation of the Pekanbaru-Dumai Toll Road. The study focuses on the UPT Regional Revenue Office in Mandau District as the primary unit of analysis. The research employs a descriptive qualitative method, with data collected through in-depth interviews with 2 key informants and secondary data obtained from documentation held by the UPT. The findings indicate that the operation of the Pekanbaru-Dumai Toll Road has significantly impacted the number of visitors to Duri City, which in turn has affected hotel tax revenue growth. The hotel tax growth rate in Duri City has dropped dramatically, from 46.9% in 2020 to 18.2% in 2023. This decline in growth rate has automatically reduced the contribution of hotel taxes to the region's own-source revenue (PAD), ultimately affecting the stability of the Regional Revenue and Expenditure Budget (APBD), which is intended to promote public welfare and regional development. The implication is that Duri City, once known as a Transit and Petrochemical City, is undergoing changes due to the decrease in visitors who stop to rest there. Keywords: Service, Growth, Tax, Hotel, Toll Road